2021
DOI: 10.1155/2021/6617541
|View full text |Cite
|
Sign up to set email alerts
|

Land Use/Land Cover Change Impact on Hydrological Process in the Upper Baro Basin, Ethiopia

Abstract: Understanding the hydrological process associated with Land Use/Land Cover (LU/LC) change is vital for decision-makers in improving human wellbeing. LU/LC change significantly affects the hydrology of the landscape, caused by anthropogenic activities. The scope of this study is to investigate the impact of LU/LC change on the hydrological process of Upper Baro Basin for the years 1987, 2002, and 2017. The Soil Water Assessment Tool (SWAT) model was used for the simulation of the streamflow. The required data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 41 publications
1
12
0
1
Order By: Relevance
“…Hence, LULC change impact on spatiotemporal assessment is substantial for socio-economic and environmental development. The findings are in agreement with studies conducted by [6,17,[20][21][22][23]29,56]. Similar studies confirmed that LULC changed from forest to agricultural land, waterbody, industrial farmland, and built-up areas.…”
Section: Assessing Hydrological Model Performance On Streamflowsupporting
confidence: 92%
See 4 more Smart Citations
“…Hence, LULC change impact on spatiotemporal assessment is substantial for socio-economic and environmental development. The findings are in agreement with studies conducted by [6,17,[20][21][22][23]29,56]. Similar studies confirmed that LULC changed from forest to agricultural land, waterbody, industrial farmland, and built-up areas.…”
Section: Assessing Hydrological Model Performance On Streamflowsupporting
confidence: 92%
“…Similar efforts in Ethiopia reported that expansion of agricultural land diminishing forest, shrubland, and grasslands increased runoff, decreasing recharge [14,23,26,36,54]. This produces flooding during the rainy season, decreasing low flow during the dry period.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations